Clinicopathological study of sinonasal masses (Bangladesh Journal of Otorhinolaryngology, 2010)
Objective: To observe the incidence, clinical presentation and to perform comparative studyof different sinonasal masses. Study design: Prospective study. Setting: Department ofotolaryngology and Head-Neck Surgery & ENT OPD of Chittagong Medical College Hospital.Patients & methods: 50 patients are included in this study (39 male & 11 female) between theages of 3 years and 80 years who were treated between August 2006 to January 2007. Studybased on history, clinical, radiological, laboratory and histopathological examination. Results:Mean age for male was 35.12 years and for female was 22.63 years. Male to female ratio was3.5:1. Highest frequency was noted in second decade. Most of patient (78%) were from poorclass. Frequency of inflammatory nasal masses were more in second decade, benign tumourin fourth and fifth decade, malignant tumour in second decade (OAN & NHL) and fifth andsecond decades (others). Rhinosporidiosis were most frequent inflammatory nasal masses.Nasal obstruction was the commonest and orbitus symptoms were less frequent symptoms.But orbital symptoms were more prevalent in malignant lesion. Conclusion: sinonasal massesare found in all age group. Rhinosporidiosis are appearing to be the commonest nasal masses.The prevalence of nasal polyp is also high. Among the malignant sinonasal masses thepercentage of squamous cell carcinoma is high.DOI: 10.3329/bjo.v16i1.5776Bangladesh J Otorhinolaryngol 2010; 16(1): 15-22